Meme Sebagai Medium Gerakan Sosial Politik ala Mahasiswa Unhas - Pamungkas, Muhammad Iqbal (Emik, 2024)
The era of modernization opens up a wide space for students to be directly involved in various forms of discourse and forums in the real space as well as virtual space. The student movement, which is always identified with taking to the streets and ending in anarchy makes society anxious, nowadays meme-based movement emerges as an alternative for students to convey their aspiration as well as critics to the authorities. While the existing literatures focus more on the use of meme as a medium for society to participate in socio-political issues, this article examines the content and effectiveness of meme-based movement of Unhas students. This qualitative research was carried out at Hasanuddin University using in-depth interview and observation as my data collection methods. Eight informants participated in this research, they consist of four activists and another four meme makers. The study shows that meme-based movement has initially emerged from personal concerns of meme makers regarding social, political, and government policies in Indonesia. This then turned into a common concern among students. Unhas students' conception of meme is related to the combination of images and writing that contains information. So far, this meme-based movement has been used by Unhas students regarding a series of issues related to the fate of lower classes, political discourse, and regulatory changes. However, memes as an alternative movement method has some weaknesses, namely the effectiveness of the movement in terms of the spread of meme content and the progress of the movement) and the short content of meme tends to rise multiple interpretations and therefore has the potential to cause misinterpretation for readerst.